Investigating the role of stakeholders in a gendered energy living lab : a case of GENS Living Lab, South Africa - Sphokazi Phelokazi, Mbatha (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.